An efficient background suppression ratio and output power using a novel fiber loop mirrors technique - Bouzid, Belloui; Mohammed, Haydar Imad; Mahdi, Mohd Adzir; Abdullah, Mohammad Khazani (ELSEVIER SCI LTD, 2007)
This paper demontrates a novel configuration of a linear cavity erbium-doped fiber laser using fiber loop mirrors to effectively suppress the noise generated by the amplified spontaneous emission (ASE). A tunable filter is deployed in each fiber loop mirror to create a narrow passband for the selected mode. The fiber laser produces high background suppression ratio (BSR) of more than 75 dB from 1525 to 1565 nm at the output coupling of 95%. There is no residual ASE detected at the output to verify the effectiveness of the noise filtering in the proposed fiber laser. Low threshold powers are obtained in the range of 2.5-3 mW and the peak power variation is smaller than 1.6 dB. (c) 2005 Elsevier Ltd. All rights reserved.